Ascribing learner development to quality schooling : a case of three schools - Modiba, N. S. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
The paper critiques how lack of quality schooling encourages grade repetition in South African public secondary schools. This paper is empirical in approach as it uses cases of selected schools in Limpopo province. Interviewing and document analysis were used to collect data from three selected public secondary schools, Capricorn District of Limpopo Province, South Africa. Research findings reveal that, firstly, an enabling learning environment contributes to quality schooling. Secondly, failure to expose learners to meteoric rise through constant scholastic performance, conditions pupils to grade repetition. Thirdly, failure to embrace the decolonisation project as a 21st century way of approaching management and leadership of teaching and learning, compromises quality schooling for pupils. Lastly, failure, to expose pupils to looping, which is allowing teachers to go to the next grade with their learners, delays pupils from coping with new teachers they face there and thus underachieve and confirm the existence of lack of quality schooling in an educational institution. As part of the conclusion, the researcher recommends for all schools to take a firm stand that one pupil underachieving in their educational institution, is one learner too many.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Environment; Grade Repetition; Looping; Underachievement; Grade repetition; Total quality management in education